2005
DOI: 10.1074/jbc.m504696200
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characterization of the Signature Domains of Thrombospondin-4 and Thrombospondin-2

Abstract: The signature domain of thrombospondins consists of tandem epidermal growth factor-like modules, 13 calcium-binding repeats, and a lectin-like module. Although very similar, the signature domains of thrombospondin-1 and -2 differ in several potentially important ways from the domains of thrombospondin-3, -4, and -5. We have compared matching recombinant segments representing the signature domains of thrombospondin-2 and -4. In the presence of 2 mM CaCl 2 , the far UV circular dichroism spectra of thrombospondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
(39 reference statements)
1
22
0
Order By: Relevance
“…Lowering the calcium concentration to 200 M, therefore, lowers the temperatures of the reversible transitions and, as in 2 mM calcium, the Ser 700 protein was more sensitive to heating than the Asn 700 protein. The four peaks seen in the THBS-1 proteins contrasts with DSC studies on the signature domain of THBS-2, which melts with two peaks (24,25) (Fig. 2C).…”
Section: The Polymorphism Leads To Altered Thermal Stability Of the Ementioning
confidence: 56%
“…Lowering the calcium concentration to 200 M, therefore, lowers the temperatures of the reversible transitions and, as in 2 mM calcium, the Ser 700 protein was more sensitive to heating than the Asn 700 protein. The four peaks seen in the THBS-1 proteins contrasts with DSC studies on the signature domain of THBS-2, which melts with two peaks (24,25) (Fig. 2C).…”
Section: The Polymorphism Leads To Altered Thermal Stability Of the Ementioning
confidence: 56%
“…Recent advances in understanding the structures of TSPs have revealed that there are extensive interactions between the EGF domains, type 3 repeats and L-lectin-like domain, such that the whole multidomain region should be considered a single structural unit (Kvansakul et al, 2004;Misenheimer and Mosher, 2005;Carlson et al, 2005). These findings are corroborated by immunochemical analyses (Annis et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These elements are three or more contiguous EGF-like modules, the Ca 2ϩ -binding wire, and the lectin-like module (4). Atomic absorption spectroscopy estimated that 28 Ca 2ϩ bind to the TSP-2 signature domain (E123CaG-2) in solution (5). This number agrees with the crystal structure, which revealed 26 Ca 2ϩ ions bound to the wire, 3 to the lectin-like module, and 1 to EGF2, for a total of 30 bound Ca 2ϩ ions (4).…”
Section: Thrombospondins (Tsp)mentioning
confidence: 99%